Identifikasi Fungsi Manajemen Sumber Daya Manusia pada Usaha Menengah (Studi pada CV Kota Agung) - Febiani Sofie (Jurnal Wacana Ekonomi, 2018)
The Indonesian economy is dominated by MSMEs (Micro, Small and Medium Enterprises). MSMEs have a very important role because they can absorb labor and also contribute to GDP (Gross Domestic Product). CV. Kota Agung is one of the MSMEs that has been established since 2006. This company also contributes to environmental sustainability by becoming a pioneer in tree planting in Indonesia. However, this company is experiencing problems in human resource management that are urgent to be addressed. This study aims to determine the managerial and operational functions contained in human resource management applied in CV. Great City. In addition, this study has another objective to determine which functions should be improved. In this study, interviews were conducted with the director, deputy director, and branch heads of CV. Kota Agung to collect the necessary data and use qualitative methods. The results of this study indicate that CV. Kota Agung has not implemented the overall managerial function of human resource management. Planning, organizing and controlling have not been implemented properly. In addition, CV. Kota Agung also has not implemented an operational function in human resource management as a whole. Procurement, development, compensation, maintenance and dismissal have not been implemented properly.